P129 The utility of routine operative swab culture in uncomplicated peri-anal abscesses. (8th April 2021) - Khajuria, Apoorva; Rahim, Tuba; Baig, Mariam; Leong, Kai
Abstract: Introduction: Despite perianal abscess being a common presentation, certain aspects of its management remain controversial, especially the routine use of intra-operative swab cultures. Methods: A retrospective review of patients that underwent incision and drainage procedures for a perianal abscess over a six-month period was undertaken. Results: Over 6 months, 50 patients were identified. The male to female ratio was 3:1 and median ASA score was 1. Only 6/50 patients presented with recurrent abscess and 1 patient had history of inflammatory bowel disease. On the basis of operative findings, 39 patients (78%) had uncomplicated abscess (not associated with cellulitis, sinus or fistula); swab cultures were performed in 26 (67%) of these patients. All patients were discharged on the same day; microbiology reports did not impact the treatment and no patients were followed up in clinic post-operatively or presented with recurrence. The number of unnecessary microbiology swabs undertaken in this cohort equates to approximately 52 unnecessary swabs a year. The cost of one swab is £10.10p, which means £520 could potentially be saved annually. Conclusion: Routine intra-operative swab cultures do not impact management decisions, add to unnecessary costs and therefore should not be undertaken in uncomplicated or first presentation of peri-anal abscesses.